2018
DOI: 10.1556/018.68.2018.1.7
|View full text |Cite
|
Sign up to set email alerts
|

Exogenous salicylic acid and cytokinin alter sugar accumulation, antioxidants and membrane stability of faba bean

Abstract: This research was conducted in a greenhouse to evaluate the effects of exogenous application of salicylic acid (SA) (1 mM) and 6-benzylaminopurine (BAP) (50 μM) on physiological performance of faba bean (Vicia faba) under different levels of NaCl salinity (0, 4, 8 and 12 dS/m). The experiment was arranged as factorial on the bases of randomized complete block design in three replications. Leaf Na content, root and leaf soluble sugars, antioxidant enzymes activities such as catalase (CAT), ascorbate peroxidase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 38 publications
(31 reference statements)
1
8
0
Order By: Relevance
“…Moreover, the content of inorganic osmotic regulatory substances increased, including Na + and Cl -, which changed in the seeds owing to a loss of control under saline stress; however, the content of soluble proteins and K + as well as the K + /Na + balance decreased. Together, these results indicate that salt stress led to membrane lipid peroxidation, which affected cotton seed germination, consistent with the results of Samea-Andabjadid et al [5] and Castanares et al [36].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Moreover, the content of inorganic osmotic regulatory substances increased, including Na + and Cl -, which changed in the seeds owing to a loss of control under saline stress; however, the content of soluble proteins and K + as well as the K + /Na + balance decreased. Together, these results indicate that salt stress led to membrane lipid peroxidation, which affected cotton seed germination, consistent with the results of Samea-Andabjadid et al [5] and Castanares et al [36].…”
Section: Discussionsupporting
confidence: 91%
“…Under salt stress, the oxidative reaction of free radicals in membrane lipids leads to the accumulation of more reactive oxygen radicals and hydrogen peroxide in plants, which causes cross-linking polymerization of proteins, nucleic acids, and other biomolecules as well as damage to the membrane system, which in turn increases malondialdehyde (MDA) content and electrolyte leakage (EL) as well as lipid peroxidation. The plant membrane system is one of the first sites initially injured by stress conditions, including high salinity [3][4][5]. Plants mainly resist salt stress damage through a series of physiological activities that includes osmotic regulation, ion transport, and hormone content change [6].…”
mentioning
confidence: 99%
“…Moreover, plant growth regulators in low concentrations always play a role in plants, and are cost-effective. Foliar spraying of salicylic acid (SA) on faba bean inhibits Na + accumulation and lipid peroxidation, improving the antioxidant resistance and finally mitigating the damage caused by salinity [18]. Exogenously applied poly-γ-glutamic acid on wheat maintains the Na + and K + homeostasis and enhances antioxidant capacity by alleviating salinity damage under salt stress conditions [19].…”
mentioning
confidence: 99%
“…Furthermore, exogenous application of CK was found to up-regulate the gene expression levels for GR and ascorbate peroxidase, resulting in oxidative stress tolerance Ma et al (2016). Samea-Andabjadid et al (2018) reported enhancement in the antioxidant activities and reduction in the lipid peroxidation in Vicia faba under salinity stress. In a recent study by Kaya et al (2019a, b), maize grown under boron toxicity demonstrated considerable oxidative stress.…”
Section: Cytokininsmentioning
confidence: 99%